2015
DOI: 10.4293/jsls.2015.00066
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Surgery for Acute Appendicitis in Children With Cancer

Abstract: Introduction:Abdominal pain during cancer chemotherapy may be caused by medical or surgical conditions. A retrospective review of 5 children with cancer who had appendicitis while receiving chemotherapy was performed.Case Descriptions:Three had acute lymphoblastic leukemia, and 1 each had T-cell lymphoblastic lymphoma and rhabdomyosarcoma. Two of the patients had a Pediatric Appendectomy Score of 6, and 1 each had a score of 7, 5, and 2. All had evidence of appendicitis on computed tomography. Laparoscopic app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Moreover, these studies support early surgical intervention in leukemic patients with appendicitis because symptoms are resolved more quickly and hospital stays are shorter [3]. Laparoscopic appendectomy appears to be the preferred procedure, resulting in a small wound, fewer wound infections, less pain, rapid recovery, and lower risk of hemorrhagic complications [4,16].…”
Section: Discussionmentioning
confidence: 81%
“…Moreover, these studies support early surgical intervention in leukemic patients with appendicitis because symptoms are resolved more quickly and hospital stays are shorter [3]. Laparoscopic appendectomy appears to be the preferred procedure, resulting in a small wound, fewer wound infections, less pain, rapid recovery, and lower risk of hemorrhagic complications [4,16].…”
Section: Discussionmentioning
confidence: 81%
“…Although not possible in all cases, our policy was to operate as soon as possible in order to avoid a "locus minoris resistantiae", which may cause www.nature.com/scientificreports/ a recurrent episode of appendicitis and/or typhlitis during the next phase of neutropenia as observed in 2 of our 21 patients. While the management of typhlitis comprises the early use of broad-spectrum antibiotics and bowel rest, appendectomy might be the treatment of choice for "pure" appendicitis 2,3,10,15,16 . Whether laparoscopic appendectomy is the preferred procedure in neutropenic children is discussed controversially.…”
Section: Discussionmentioning
confidence: 99%
“…In general, appendectomy seems to be a better choice of treatment for acute appendicitis. 5,[9][10][11] However, in the neutropaenic phase of HSCT, appendectomy is an extremely tough choice for surgeons and haematologists, 12 and none of the patients in such a condition were transferred to receive appendectomy. In this study, we showed that acute appendicitis that occurred in patients during the neutropaenic phase of HSCT could be resolved with internal methods that use a combination of different kinds of full dose broad-spectrum antibiotics, bowel rest and total parenteral nutrition.…”
mentioning
confidence: 99%